Salad Consumption in Relation to Daily Dietary Intake and Diet Quality among U.S. Adults, 2003-2012 - Ruopeng An; Naiman Khan (Epidemiology, Biostatistics and Public Health)
Backgrounds: This study examined salad consumption in relation to daily dietary intake and diet quality among U.S. adults.